Acute Urinary Retention Cuased by Biperiden in a Female Patient: A Case Report - Gonenir Erbay, Lale; Aydin, Yusuf; Yesil, Bahar; Karlidag, Rifat (Annals of Medical Research, 2021)
None
Keywords: Anticholinergic; Biperiden; Urinary Retention.